Research progress on hydrogen embrittlement in hydrogen-blended natural gas transportation system - Weiqing XU; Yanghui LU; Chen SUN; Guanwei JIA; Mengya LI; Mingyu LEI; Maolin CAI; Sujun WU (You-qi chuyun, 2022)
Hydrogen-blended natural gas transportation can effectively solve the problem of wind and photovoltaic energy curtailment and reduction of greenhouse gas emission, and realize the low-cost transportation of hydrogen in large scale, so it becomes an important way to achieve the "double carbon" goal. However, the risk of hydrogen embrittlement will be brought by blending hydrogen to the existing natural gas pipeline system and relevant transportation facilities. Therefore, the mechanism of hydrogen embrittlement was analyzed based on the structural composition of hydrogen-blended natural gas transportation system. Meanwhile, investigation was performed for the hydrogen embrittlement of the pipelines, welds, valves, compression devices, storage units and terminals of the hydrogen-blended natural gas transportation system. On this basis, countermeasures for prevention of hydrogen embrittlement were put forward. Then, the prospect and development of hydrogen-blended natural gas transportation system were forecast. Generally, the research results could provide reference for the large-scale and market-oriented development of hydrogen-blended natural gas transportation in China, and the improvement of research and development of pipeline hydrogen transportation technology and equipment, further accelerating the safe development of hydrogen economy.